Assessment of contaminant concentrations in sediments, fish and mussels sampled from the North Atlantic and European regional seas within the ICON project. (March 2017) - Robinson, Craig D.; Webster, Lynda; Martínez-Gómez, Concepción; Burgeot, Thierry; Gubbins, Matthew J.; Thain, John E.; Vethaak, A. Dick; McIntosh, Alistair D.; Hylland, Ketil
Abstract: Understanding the status of contaminants in the marine environment is a requirement of European Union Directives and the Regional Seas Conventions, so that measures to reduce pollution can be identified and their efficacy assessed. The international ICON workshop (Hylland et al., 2017) was developed in order to test an integrated approach to assessing both contaminant concentrations and their effects. This paper describes and assesses the concentrations of trace metals, polycyclic aromatic hydrocarbons, and polychlorinated biphenyls in sediments, mussels, and fish collected from estuarine, coastal and offshore waters from Iceland to the Mediterranean Sea. For organic contaminants, concentrations progressively increased from Iceland, to the offshore North Sea, to the coastal seas, and were highest in estuaries. Metals had a more complex distribution, reflecting local anthropogenic inputs, natural sources and hydrological conditions. Use of internationally recognised assessment criteria indicated that at no site were concentrations of all contaminants at background and that concentrations of some contaminants were of significant concern in all areas, except the central North Sea. Graphical abstract: Highlights: Sediments, fish and mussels were collected from Iceland to the Mediterranean Sea. Concentrations of organics were lowest at Iceland and highest in the Seine estuary. Concentrations of metals were highest at Cartagena in the Mediterranean Sea. At most sites, concentrations of at least one contaminant were of significant concern.